Experimental research on tape spring supported space inflatable structures. (January 2016) - Cook, Andrew J.; Walker, Scott J.I.
Abstract: This paper presents experimental research that continues the development of inflatable hybrid structures for space applications. Inflatables provide a concept with much scope for further incorporation into the structures of future spacecraft. They offer considerable savings in mass and stowed volume for spacecraft, providing possible reductions in satellite costs. Existing boom configurations make use of inflatables including solar arrays and the NGST sunshield. However these typically soft systems could be improved by incorporating tape springs as structural stiffeners along the length of the boom, creating hybrid structures. This research builds on previous experimental work undertaken at the University of Southampton looking at cantilever inflatable and hybrid booms. The focus of this research is to identify the structural performance improvement of adding tape springs to cantilever inflatable booms. This is achieved by tip deflection testing to determine the bending moment and rigidity performances of these structures allowing a comparison between the two technologies. Several hybrid booms are created and tested in various orientations to identify the optimal tape spring effectiveness. It was found that adding a pair of tape springs will increase stiffness of the hybrid structure by up to 4.9 times for an increase of 2.4 times the boom mass. Highlights: A Nylon inflatable boom has a maximum failure bending moment of 25 Nm at 15 psi. Attaching two steel tape springs increase the failure bending moment to 41 Nm. Boom rigidity increases from 0.83 to 4.06 kN/m between inflatable and hybrid booms. Two opposed tapes inline with the applied load give the greatest structural benefit.